2013
DOI: 10.1155/2013/983580
|View full text |Cite
|
Sign up to set email alerts
|

Nonsyndromic Familial Oligodontia with Multiple Dens Invaginatus: A Case Report of an Unusual Case

Abstract: Oligodontia is a rare dental anomaly with a prevalence of 0.3% in permanent teeth and much less frequency in the primary dentition. Familial oligodontia represents an absence of varying numbers of primary and/or secondary teeth as an isolated trait. It is a complex and multifactorial condition. Many explanations—evolutionary, genetic, and environmental—have been proposed as the etiology. Simultaneous with oligodontia are often the different positional changes of the existing teeth, their morphology, size, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Several dental anomalies, such as microdontia, taurodontism, and supernumerary teeth, were usually related to bilateral DI [22]. To support this tendency, Vinuth et al [23] reported an unusual case of nonsyndromic familial oligodontia combined with multiple DI. Besides, the syndromic relation between DI with Ekman-Westborg-Julin syndrome, Williams syndrome, and Nance Huran syndrome has been reported [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several dental anomalies, such as microdontia, taurodontism, and supernumerary teeth, were usually related to bilateral DI [22]. To support this tendency, Vinuth et al [23] reported an unusual case of nonsyndromic familial oligodontia combined with multiple DI. Besides, the syndromic relation between DI with Ekman-Westborg-Julin syndrome, Williams syndrome, and Nance Huran syndrome has been reported [24].…”
Section: Discussionmentioning
confidence: 99%
“…Чаще всего инвагинированными являются верхние латеральные резцы, однако встречаются случаи инвагинации центральных резцов, клыков, премоляров и моляров [ 2 ] . В литературе описаны как изменения в симметричных зубах, так и сочетания с другими аномалиями: гипо-, гипер-и макродентией [ 3,4 ] . Существует несколько теорий возникновения инвагинации зуба: инфицирование и травмы, быстрая пролиферация внутреннего эмалевого эпителия в подлежащий зубной сосочек.…”
Section: ; 26 (2) апрель-июньunclassified

Lateral incisors treatment: a case report

Павловская,
Митропанова,
Газарова
et al. 2023
Clinical Dentistry (Russia)
“…5,6 Although there have been reports of missing teeth in family members but most of these studies have reported cases with four to six missing teeth or oligodontia. [7][8][9][10][11][12][13] The present article reports a case of hypodontia involving permanent teeth in four members of a family. The unique feature of this report is that three members of a family consistently had single maxillary lateral incisor missing with concomitant microdontia of contralateral maxillary lateral incisor.…”
Section: Introductionmentioning
confidence: 99%